ANALISIS DAN PERANCANGAN DECISION SUPPORT SYSTEM PENYALURAN BANTUAN PENYANDANG MASALAH KESEJAHTERAAN SOSIAL (PMKS) MENGGUNAKAN METODE WEIGHTED PRODUCT (WP): STUDI KASUS : DI KELURAHAN SARIHARJO - Ahmad Mukhlasin; Putri Taqwa Prasetyaningrum (Antivirus : Jurnal Ilmiah Teknik Informatika, 2020)
Abstract : Through Social Welfare Law No. 11 of 2009 and PERMENSOS 08 of 2012, the government made efforts to improve the social welfare of PMKS (People with Social Welfare Problems). So far, PMKS participants have still used manual identification, so there is a lack of acceptance or acceptance by PMKS participants. Participation of participants. Then an alternative solution using DSS. Then alternative solutions can use DSS. For reception to be targeted, it is necessary to use ranking methods or which order is more priority in receiving assistance. Before that, it is necessary to do an interview & observation of related parties about what categories and criteria the community enters into PMKS members. Then to find out their priorities, in this study using the Weighted Product calculation method. The design of this DSS uses 12 PMKS Categories, each of which has criteria, and then is calculated. The results from the lowest to highest values ​​can be seen in each of the PMKS Categories. Later it will be seen who is more priority per category. The highest final acquisition value (V) is in the neglected children category 0.1503, the disabled children category 0.3610, the elderly abandoned category 0.1725, the disability category 0.1141, the socioeconomic-prone women category, and the socially difficult family category psychological 0,2301. Key words : Decision Support System, PMKS, Weighted Product (WP).